Pilot Commercialization of Improved Cookstoves in Nicaragua - Terrado, Ernesto N.; Eitel, Birgit (World Bank, Washington, DC, 2014)
The problems facing the fuel wood sector in Nicaragua can be summarized as follows: First, almost all harvest or production is based on non-sustainable forestry, with little or no regulation or enforcement of wood cutting laws, no incentives for conservation and no long-term supply-side planning. Second, almost all fuel wood is consumed by users in low efficiency stoves or kilns, and no demand-side management efforts have been carried out. Although wood is the major energy source and forest product of Nicaragua, and strongly linked to the lives of the poor, there appears to be no government agency charged with the planning and modernization of this sector. The present ESMAP technical assistance activity strongly emphasizes the role of the private sector in improved stoves dissemination. Its expected outcomes were: 1) useful knowledge gained by small private stoves producers of more efficient, less polluting stoves designs, 2) considerably heightened public awareness of the health impacts of traditional open fire stoves used in typical closed kitchens, and hence appreciation of the health benefits of improved stoves; and 3) reduction of indoor pollution where feasible through promotion of the use of high efficiency stoves equipped with chimneys that vent emissions outside the house. The technical assistance activity would catalyze the commercialization of improved cookstoves in Nicaragua by improving the understanding of consumer preferences, developing an effective dissemination strategy, selecting financially viable high-efficiency models which satisfy consumer preferences, training and supporting private entrepreneurs to manufacture and sell the stoves in a financially sustainable manner, and supporting development of credit networks for stove purchases. The specific objectives were to improve the kitchen and household environment, reduce indoor pollution and lower cooking costs. Further, the project would support the efficient use of fuel wood and, thus, help to protect biomass resources.